Mieczysław Rulikowski i nienapisana monografia .......... 123 - Jędrzejczyk, Anna („Szalony, kto nie chce wyżej, jeżeli może”: Studia i materiały do badań nad życiem i twórczością Heleny Modrzejewskiej, 2025)
MIECZYSŁAW RULIKOWSKI AND THE UNWRITTEN MONOGRAPHYHelena Modjeska has reminded us of the figure of Mieczysław Rulikowski, scientist and polymath of the turn of the 20th century: bookseller, librarian, bibliographer, art and theater historian, and eminent archivist. A considerable part of his archive, which he left with The Institute of Art of the Polish Academy of Sciences, refers to the history of Polish theater and includes materials related to the actress: photographs and letters as well as various slips with handwritten notes by Rulikowski, who intended to write a monography of the Polish actress. The work on this book was stopped short by his death. The article attempts to describe his plans.